Vicarious Trauma in Natural Disaster Volunteers - Gito Febrian, Gito; Wahidah Fitriani; Putri Yeni; Pong, Ming; Kiri, Ming (Darussalam: Journal of Psychology and Educational, 2025)
Natural disasters have a significant impact on the psychological well-being of volunteers involved in post-disaster management and recovery processes . This research examines the phenomenon of vicarious trauma experienced by natural disaster volunteers, identifying symptoms such as excessive anxiety, depression, sleep disorders, and physical symptoms including chronic fatigue and headaches. Factors that influence the level of vicarious trauma include social support, previous trauma experiences, coping strategies , and resilience , as well as organizational factors such as supervisory support and workload. This research also highlights the importance of self-care strategies , social support, training, and supportive organizational approaches in overcoming vicarious trauma. Consistent implementation of these strategies can support volunteers' psychological well-being and increase the overall effectiveness of disaster relief.